Mechanism Underlying Heat Stability of the Rice Endosperm Cytosolic ADP-Glucose Pyrophosphorylase - Hwang, Seon-Kap; Singh, Salvinder; Maharana, Jitendra; Kalita, Samhita; Tuncel, Aytug; Rath, Tanmayee; Panda, Debashish; Modi, Mahendra Kumar; Okita, Thomas W. (Frontiers in Plant Science, 2019)
Rice grains accumulate starch as their major storage reserve whose biosynthesis is sensitive to heat. ADP-glucose pyrophosphorylase (AGPase) is among the starch biosynthetic enzymes severely affected by heat stress during seed maturation. To increase the heat tolerance of the rice enzyme, we engineered two dominant AGPase subunits expressed in developing endosperm, the large (L2) and small (S2b) subunits of the cytosol-specific AGPase. Bacterial expression of the rice S2b with the rice L2, potato tuber LS (pLS), or with the mosaic rice-potato large subunits, L2-pLS and pLS-L2, produced heat-sensitive recombinant enzymes, which retained less than 10% of their enzyme activities after 5 min incubation at 55°C. However, assembly of the rice L2 with the potato tuber SS (pSS) showed significantly increased heat stability comparable to the heat-stable potato pLS/pSS. The S2b assembled with the mosaic L2-pLS subunit showed 3-fold higher sensitivity to 3-PGA than L2/S2b, whereas the counterpart mosaic pLS-L2/S2b showed 225-fold lower sensitivity. Introduction of a QTC motif into S2b created an N-terminal disulfide linkage that was cleaved by dithiothreitol reduction. The QTC enzyme showed moderate heat stability but was not as stable as the potato AGPase. While the QTC AGPase exhibited approximately fourfold increase in 3-PGA sensitivity, its substrate affinities were largely unchanged. Random mutagenesis of S2bQTC produced six mutant lines with elevated production of glycogen in bacteria. All six lines contained a L379F substitution, which conferred enhanced glycogen production in bacteria and increased heat stability. Modeled structure of this mutant enzyme revealed that this highly conserved leucine residue is located in the enzyme’s regulatory pocket that provides interaction sites for activators and inhibitors. Our molecular dynamic simulation analysis suggests that introduction of the QTC motif and the L379F mutation improves enzyme heat stability by stabilizing their backbone structures possibly due to the increased number of H-bonds between the small subunits and increased intermolecular interactions between the two SSs and two LSs at elevated temperature.